2009
DOI: 10.1038/cmi.2009.35
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Expression of a Novel Human Transcriptional Repressor HMBOX1 and Preparation of Anti-HMBOX1 Monoclonal Antibody

Abstract: HMBOX1 was a novel transcription factor possibly involving in function of pancreas and cytotoxicity of NK cells. For function determination, recombinant human HMBOX1 protein was obtained and purified, and the monoclonal antibodies against HMBOX1 were prepared. The full-length cDNA fragment encoding HMBOX1 was amplified from NK-92 cells and inserted into prokaryotic expression vector pET22b. The pET22b-HMBOX1-6his vector was then transformed into E. coli Rosetta (DE3) and induced by 1 mM IPTG for 4 h at 37 o C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Previous research has confirmed that HMBOX1 is widely expressed in human tissues (4). Here, the expression profile of HMBOX1 was further identified in various human tumors.…”
Section: Abnormal Expression Of Hmbox1 In Carcinoma Tissuesmentioning
confidence: 65%
See 1 more Smart Citation
“…Previous research has confirmed that HMBOX1 is widely expressed in human tissues (4). Here, the expression profile of HMBOX1 was further identified in various human tumors.…”
Section: Abnormal Expression Of Hmbox1 In Carcinoma Tissuesmentioning
confidence: 65%
“…hmBOx1 is highly conserved in humans, mice, rats, chickens and xenopus (2), and is detected in both the cytoplasm and nucleus of 10 normal human tissues, including the cerebrum, pancreas, kidney and liver (4). co-transfection of hEK-293t cells with the pm-hmBOx1 plasmid and reporter plasmid pGal4 5 tkluc indicates that the hmBOx1 protein may be a transcription repressor, while hmBOx1b only retains faint transcriptional repressive activity (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…The colorimetric signal was measured at OD 450nm and OD 630nm . The specification and affinity constant of the monoclonal antibodies were determined by competitive ELISA as previously described [24,25].…”
Section: Elisamentioning
confidence: 99%
“…The anti-HMBOX1 monoclonal antibody used for western blot analysis was prepared by our lab. 5 Monoclonal mouse anti-human NKG2D mAb (R&D Systems) was used to stimulate NK cells.…”
Section: Antibodiesmentioning
confidence: 99%
“…1, 5 Chen et al speculated that HMBOX1 may be a ubiquitous transcription repressor that is expressed in most human tissues. 1 Recently, Su et al reported that HMBOX1 is a key factor in the differentiation of bone marrow stromal cells into vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%